Church and estate : religion and wealth in industrial-era Philadelphia - Rzeznik, Thomas F., 1979- (Pennsylvania State University Press, 2013)
"Examines the lives and religious commitments of the Philadelphia elite during the period of industrial prosperity that extended from the late nineteenth century through the 1920s"--Provided by publisher